Impact Assessment of Oron Inland Waterways Transport System on the Growth and Development of Oron Coastal Community and Environs - Gabriel M. Eto; Nse B. Okon (ESUT JOURNAL OF SOCIAL SCIENCES, 2025)
The paper examines the impact of Oron inland waterways transport system on the growth and development of Oron coastal community and environs. It evaluates eight objectives that mirrored the research problem and adopts cross-sectional survey design to examine the population of study. It uses multi-stage sampling techniques that involved stratified and random sampling techniques to select the sample. Out of a population of 1,873, Taro Yamane formula was used to determine the sample size of 363. In order to analyze the data gathered, descriptive statistics was used. The study adopted simple random sampling technique due to its ease of use and accuracy of representation. From interviews, literature review, media reports and critical stakeholders’ opinions, the study examines the economic impact of the Oron inland waterways transport system and notes that it enhances the efficiency of local businesses by reducing transportation costs, and it facilitates increased trade and creates employment opportunities. The study identifies the challenges facing Oron inland waterways transport system and finds that they could be tackled through coordinated efforts of government agencies, transport operators, local communities, and businesses in order to enhance safety measures, improve infrastructure, and strengthen security protocols. Consequently, the study recommends, among others, that equitable resource allocation to Oron waterways transport system is necessary in light of its significance in enhancing connectivity towards promoting trade and commerce, job creation, and trade cost reduction.